2018
DOI: 10.13005/ojc/3404047
|View full text |Cite
|
Sign up to set email alerts
|

Excess Molar Quantities of Binary Mixture of Dipropyl amine with Aliphatic Alcohols at 298.15 K

Abstract: Refractive indices (nD), viscosities (η) and densities (ρ) were deliberated for the binary mixtures created by dipropyl amine with 1-octanol, 1-heptanol, 1-hexanol, 1-pentanol and tert-pentyl alcohol at temperature 298.15 K over the perfect installation extent. The function of Redlich-Kister were used to calculate and renovated of the refractive index deviations (∆nD), viscosity deviations (ηE), excess molar Gibbs free energy (∆G*E) and excess molar volumes (VmE) The standard errors and coefficients were resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…15 0.7711 0.77113 13 1258.84 1259.27 13 1.3390 1.33906 13 0.771130 14 1263.9 16 1.3394 15 0.7715200 16 1268 17 1.3390 18 0.771487 17 1258.81 21 0.771200 21 313. 15 0.7601 0.76018 13 1218.51 1218.56 13 1.3342 1.33423 13 0.760900 16 1226.5 16 1.3348 15 T h i s c o n t e n t i s 75 1.4179 1.4172 76 0.818 76 1.41826 46 0.81880 42 1.4178 77 0.8189 46 1.4168 81 1303.8 82 1.4158 83 0.8149 76 1302.42 75 1.4148 78 0.81526 42 1303.5 84 1.41610 85 0.8151 83 1.41775 53 0.8154 78 1.4154 86 0.81503 53…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 0.7711 0.77113 13 1258.84 1259.27 13 1.3390 1.33906 13 0.771130 14 1263.9 16 1.3394 15 0.7715200 16 1268 17 1.3390 18 0.771487 17 1258.81 21 0.771200 21 313. 15 0.7601 0.76018 13 1218.51 1218.56 13 1.3342 1.33423 13 0.760900 16 1226.5 16 1.3348 15 T h i s c o n t e n t i s 75 1.4179 1.4172 76 0.818 76 1.41826 46 0.81880 42 1.4178 77 0.8189 46 1.4168 81 1303.8 82 1.4158 83 0.8149 76 1302.42 75 1.4148 78 0.81526 42 1303.5 84 1.41610 85 0.8151 83 1.41775 53 0.8154 78 1.4154 86 0.81503 53…”
Section: Introductionmentioning
confidence: 99%
“…Some hydrocarbons, especially (benzene, toluene, xylenes) are absorbed in the alkanolamine solution . Several studies have reported the importance of thermophysical and thermodynamics properties of liquid mixtures for possible industrial applications. …”
Section: Introductionmentioning
confidence: 99%
“…fluids flow, heat and mass transfer) of mixtures systems are important in many chemical industries, solution theories and biological processes [1][2][3][4]. Moreover, for profound understanding the interaction properties between component molecules of liquid mixture, in terms of nature, strength of interaction and behavior of solution, the experimental excess properties are very important [5][6][7][8].…”
Section: Introductionsmentioning
confidence: 99%